?EFFECT OF WEEDING ON THE YIELD OF WHEAT (Biological Sciences - PJSIR, 1999)
A 2 year field experiment was conducted at the Regional Agricultural Research Station of BARI, Ishurdi during NovembertoMarch 1991-92& J 992-93witheightweedingtreatmentssuchascontinuousweeding(control),weedfree upto 20,30and40 daysafteremergenceofcrop,noweeding,weedingafter20,30and40 daysafteremergence ofcrop. The main infesting species of weed was Cyperus rotundus. The grain yield and yield components were significantly influenced byweedcompetitiontreatments.Thegreatertheweedcompetitionperiod,thegreaterwasthecrop loss.The criticalperiodofweedcompetitionrangedfrom20to30daysafteremergence.Thegrainyieldlossesduetounrestricted weed growth throughout the crop cycle was 25.7%.